Banking sectors' international interconnectedness: Implications for consumption risk sharing in Europe - Thomas Nitschka (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Cross-border asset and liability holdings allow countries to insulate their consumption streams from idiosyncratic output shocks, i.e. consumption risk sharing. More cross-border asset holdings are associated with more risk sharing. By contrast, a bank's interconnectedness is regarded as an indicator of its exposure to systemic risk. International interbank asset holdings could hence positively or negatively affect international consumption risk sharing. This paper provides evidence in favour of the latter hypothesis. A country's ability to achieve consumption risk sharing decreases if banks located in that country are strongly linked to other countries' banks.
Keywords: G20; F15; E44; 330; banking sector; cross-border assets; consumption risk sharing; interconnectedness; systemic risk